Adherence patterns, risk factors and complications among patients with tuberculosis: a cross-sectional study at Nsawam Government Hospital - Abraham Norman Nortey; Amanda Adjoda; Amidu Alhassan; Godfred Yawson Scott (BMJ Public Health)
Background Tuberculosis (TB) is the ninth leading cause of death worldwide, and the leading cause of death from a single infectious agent prior to COVID-19 pandemic. TB substantially affects adults during their most productive years. However, all age groups are at risk. More than 25% of cases and deaths occur in Africa. People infected with HIV are 20–30 times more likely to develop active TB. In this study, we determined the level of TB medication adherence, risk factors and complications of TB in outpatients attending the Nsawam Government Hospital.Method This cross-sectional study randomly recruited 277 patients with TB attending the Nsawam Government Hospital for care. Structured questionnaires were used to collect sociodemographic information, adherence and lifestyle characteristics. Associations and multivariate logistic regression analysis were performed with 95% CIs. All p<0.05 were considered statistically significant.Results Majority (36.1%) of the patients were between the ages of 29 and 38. Majority (63.9%) of them had high adherence to TB medication. Participants earning less than 500 Ghana Cedis (Ghc) (adjusted OR (aOR)=8.85. 95% CI (1.59 to 49.24), p=0.013), patients with TB who indicated having complication (joint pain, spinal pain, heart disorders, liver or kidney problems) as a result of TB (aOR=2.81, 95% CI (1.58 to 4.99), p<0.001), respondents who mentioned living with people infected with TB (aOR=3.23. 95% CI (1.24 to 8.37), p=0.016) were the independent predictors of adherence to TB medication.Conclusion The study findings revealed that participants exhibited commendable adherence to TB medication. Notably, adherence levels were found to be linked to several factors, including income, medication side effects and cohabitation with individuals infected with TB. The positive trend in adherence underscores the importance of considering socioeconomic factors, as lower income was identified as a potential barrier to consistent medication adherence